Potensi dan keragaman hayati cagar alam Bukit Bungkuk - Salman Yasir; Eko Sutrisno (Jurnal Zona, 2019)
The area of Bukit Bungkuk wildlife sanctuary is on Kampar regency in Riau Province. Based on the decree of Minister of Forestry at 3917/Menhut-VII/KUH/2014 which were areas 12.828,88 Ha. The existence of Bukit Bungkuk wildlife sanctuary is a habitat for the endangered and the protected flora and fauna. Monitoring of the existence these areas was carried out in a rapid survey and interview with village officials and local communities. These activities to obtain the existence and the potential of carrying capacity of Bukit Bungkuk wildlife sanctuary. This area is a home to 32 species of wildlife found directly or indirectly. Furthermore, there are 2 potentials environmental services in this area that can be developed on empowerment schemes to the edging local community. The potentials of environmental services are Koto Panjang reservoir and several waterfalls around and in the area. Currently, the utilization of environmental services was carried out by the community and based on natural sustainability with the local wi